Small molecule innate immune modulators in cancer therapy - Goswami, Avijit; Goyal, Sandeep; Khurana, Princy; Singh, Kawaljit; Deb, Barnali; Kulkarni, Aditya (Frontiers in Immunology, 2024)
Immunotherapy has proved to be a breakthrough in cancer treatment. So far, a bulk of the approved/late-stage cancer immunotherapy are antibody-based. Although these antibody-based drugs have demonstrated great promise, a majority of them are limited challenged due to by their access to only extracellular targets, lack of oral bioavailability, tumor microenvironment penetration, induction of antibody dependent cytotoxicity etc. In recent times, there has been an increased research focus on the development of small molecule immunomodulators since they have the potential to overcome the aforementioned limitations posed by antibodies. Furthermore, while most biologics based therapeutics that are in clinical use are limited to modulating the adaptive immune system, very few clinically approved therapeutic modalities exist that modulate the innate immune system. The innate immune system, which is the body's first line of defense, has the ability to turn cold tumors hot and synergize strongly with existing adaptive immune modulators. In preclinical studies, small molecule innate immune modulators have demonstrated synergistic efficacy as combination modalities with current standard-of-care immune checkpoint antibodies. In this review, we highlight the recent advances made by small molecule innate immunomodulators in cancer immunotherapy.